Early Learning Assessment Innovation in South Africa: A locally appropriate monitoring tool. Issue 1 (2nd January 2018) - Dawes, Andrew; Biersteker, Linda; Girdwood, Elizabeth; Snelling, Matthew; Tredoux, C. G.
Abstract : Innovation in education goes beyond curriculum and content delivery. We also must look for ways to ensure that how we assess our education programs is relevant and current.